INVESTIGATION OF LIGHTWEIGHT STRUCTURAL MATERIALS PRODUCED USING ALUMINUM SCRAPS WITH CEMENT MORTAR - NOORI, ABDUL_QADER NIHAD; ALIEWI , JASSIM MUHSIN; SALMAN, HEBA KADHM; NUMAN , HESHAM A. (Journal of Applied Engineering Science, 2021)
A lot of environmental concerns are increasing day after day result in the raise of solid waste in large quantities in the world resulting from the demolition of buildings and various industrial and commercial activities. This research provides the possibility of reusing one of these wastes solid aluminum scrap (Als) by using it to produce a modified type of cement mortar. The research focuses on the mechanical behavior of the new cement mortar type obtained by adding aluminum scrap by different percentages (1%, 2%, 3%, 4%, and 5%) as a replacement ratio from the weight of sand mixed with Ordinary Portland Cement (OPC). The findings of this research indicated the possibility of using aluminum waste material in certain limits where the compressive strength significantly reduced by increasing the percentage of Als. The most interesting observation was to increase the volume of the mixture by increasing the ratio of Als. According to the results, it is possible to use this type of cement mortar to produce lightweight structural members such as slabs, bricks, etc. Finally, the general formulation was proposed based on the regression analysis and experimental measurements to give a capture of the compressive strength of mortar under any variables alter (age of specimen and/or quantity of aluminum replacement).
Keywords: aluminum scraps; compressive strength; fine aggregate; lightweight; sustainable